Impact Assessment of Consumer Demographics on Rural Consumers' Ethnocentric Tendencies (CE) and Social Comparison Information (ATSCI) Habits - Das, Manish; Saha, Victor (Indian Journal of Marketing, 2018)
Growth for firms in India requires more and more penetration into the rural markets as urban markets in India are witnessing stagnation. Generalizing urban consumer research findings to formulate rural market strategies may not pave way for rural penetration. Firms need more and more rural specific consumer research to formulate their strategies to excel in rural markets. The present paper is one of such kind and analyzed the role of demographics in shaping rural consumers' ethnocentric (CE) and social comparison (ATSCI) tendencies - two powerful consumer market segmentation variables. It also assessed the likelihood of accepting communication messages having joint and independent appeal of CE and ATSCI. By adhering to appropriate research mechanisms, the study collected and analyzed data from 153 rural consumers belonging to both tribe and non-tribe categories from Tripura, a land locked hilly state of North East India. Data analysis was carried out by using confirmatory factor analysis, one-way ANOVA, independent sample 't' test, and non - parametric Friedman test. The study confirmed ATSCI as one of the significant constructs in shaping rural purchase behaviour. It also highlighted age and education as the significant predictors of ethnocentric tendencies and gender for social comparison tendency. Older and less educated people were found to be more ethnocentric ; whereas, women were found to make greater social comparisons than men. The possible applications of these findings in the context of rural marketing were also discussed.